Separation of closed circular DNA from linear DNA by electrophoresis in two dimensions in agarose gels. - Oppenheim, A (1981)
A method that provides an easy, rapid, and reproducible way for separating closed circular DNA species from linear DNA and nicked circles is described. The method is based on the difference in mobility of form I (supercoiled) DNA and form II (nicked circles), and the differential mobility of relaxed circular DNA in the presence and absence of ethidium bromide (EtdBr). It can be used for detection or for purification of plasmid, episomal, or viral DNA from the bulk of cellular DNA, or from other DNA mixtures.